Perlakuan Akuntansi Pendapatan Jasa Outsourcing Pada Pt. Ion Solusi Objektif - Ferry Dermawan; Yenni Samri Juliati Nasution (Serat Acitya, 2022)
The income earned by companies in the field of outsourcing comes from all forms of work contracts and also management fees, which means that it comes from all kinds of service revenue in the field of outsourcing as income obtained directly from all areas of sales activity in the service sector. Outsourcing in the field of companies comes from the existence of work agreements, as a form of income accounting treatment at the Ions Solusi Objective company. The main part in managing the company is in the field of recognition, presentation and measurement. The methods used in this study were interviews and documentation as the main part of the data analysis as the main part of the qualitative descriptive. The results of the study are that there is an accounting treatment that originates from outsourcing service revenue from PT. Ion Solution Objective seen from the recognition, presentation, and measurement. Revenue from outsourcing services is in accordance with the rules that apply in SAK ETAP